2016
DOI: 10.9744/jti.18.1.51-62
|View full text |Cite
|
Sign up to set email alerts
|

Change Management Perspectives in an ERP Module Implementation: A Case Study in a Telecommunication Company

Abstract: Successful Enterprise Resource Planning (ERP) projects require change management to support the integration of the ERP systems into work environment because ERP implementations involve lots of changes on technical infrastructures, business processes, organization structure, rules and skills of people in the organization. This study was aimed to explain the challenges in implementing an ERP module in a Indonesian telecommunication company, focusing on the change management process involves in the project. A cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The role of change management is considerably significant in the implementation of ERP systems particularly in minimizing change resistance that can potentially result in the failure of ERP system implementation (Nasution, 2010). The study of change management generally centers on how appropriate the strategies allow the transition from organizational resistance to organizational acceptance of the use of a system (Al-Nafjan & Al-Mudimigh, 2011;Aladwani, 2001;Alballaa & Al-Mudimigh, 2011;Simatupang et al, 2016). Despite its significance, it seems that there is still very limited research that has identified the factors that take into account the aspects of successful change management within ERP implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The role of change management is considerably significant in the implementation of ERP systems particularly in minimizing change resistance that can potentially result in the failure of ERP system implementation (Nasution, 2010). The study of change management generally centers on how appropriate the strategies allow the transition from organizational resistance to organizational acceptance of the use of a system (Al-Nafjan & Al-Mudimigh, 2011;Aladwani, 2001;Alballaa & Al-Mudimigh, 2011;Simatupang et al, 2016). Despite its significance, it seems that there is still very limited research that has identified the factors that take into account the aspects of successful change management within ERP implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies (e.g. Genoulaz et al, 2005;Govindaraju, 2012;Simatupang et al, 2016) have emphasised that going live is not the end of an ERP implementation. On the contrary, it is the end of the beginning of a Govindaraju et al 579 journey towards improvement, innovation and agility.…”
Section: Introductionmentioning
confidence: 99%